EFFECT OF GLUTAMATE ON AUTOPHAGY INDUCED BY ENERGY STRESS IN SH-SY5Y NEURONS - Vukotić, Tatjana M; Trajković, Vladimir (Medicinski podmladak, 2017)
Abstract Introduction: Autophagy is a cytoprotective mechanism by which cells adapt to stress. In neurons, the question whether enhanced autophagy promotes cell death or cell survival is a subject of considerable debate, especially in excitotoxic conditions such as cerebral ischemia. Excitotoxicity is a pathological process that involves overstimulation of the excitatory receptors, primarily the ionotropic and metabotropic glutamate receptors. Material and methods: The viability of neuroblastoma SH-SY5Y cells was investigated by MTT assay for mitochondrial dehydrogenase activity. The appearance of autophagolysosomes and autophagic flux were determined by acridine orange staining (AO) and immunoblot, and the expression of autophagic genes was assessed by quantitative RT-PCR. Results: Viability test showed a decrease in cell numbers, while AO test demonstrated a decrease in number of acidic vesicles in HBSS medium with glutamate compared to HBSS medium alone. Accumulation of autophagosome-asociated LC3-II protein was observed by immunoblot in HBSS medium, while LC3-II levels were lower in HBSS medium with glutamate. Quantitative RT-PCR showed reduced expression of the autophagy genes in HBSS medium with glutamate compared to the HBSS medium. Conclusion: The research confirmed that glutamate during energy deprivation in vitro leads to a decrease in autophagy in neurons, possibly preventing the induction of autophagy by reducing the transcription of autophagy genes. Keywords: autophagy, excitotoxicity, glutamate.